Implementasi Algoritma Traveling Salesman Problem (TSP) dalam Penentuan Jalur Terpendek pada Rute Berlayar untuk Kegiatan Aplousing dan Perawatan SBNP di Wilayah Kerja Kantor Distrik Navigasi Tipe A Tanjung Perak - Adil Wanadi, M.; Irfan Efendi, Ade Irfan Efendi; Prakosa, Dandun; Rizal, Yus (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2026)
The aplousing and maintenance activities of Shipping Navigation Assistance Facilities (SBNP) in the work area of the Tanjung Perak Type A Navigation District provide high efficiency in fuel use and travel time while minimizing the impact of environmental pollution. However, the shipping route so far has not been optimal, resulting in longer mileage, requiring excess fuel consumption and increased exhaust emissions. This study aims to optimize shipping routes through the application of the Traveling Salesman Problem (TSP) algorithm. The two approaches used are Heuristic Nearest Neighbor and Brute Force with case studies on 11 port points and islands in the waters of East Java. The simulation results showed that the Brute Force approach produced the most optimal route with a total distance of ±1,095.94 km more efficient than the Nearest Neighbor ±1,110.33 km and the initial route without optimization of ±1,284.3 km. This reduction in mileage has a positive impact on fuel savings, shipping time and reducing exhaust emissions. This study proves that the application of the TSP algorithm is able to increase operational efficiency and has the potential to be the basis for the development of technology-based decision-making support systems in environmentally friendly shipping route management.